The Role of Time Preferences in Educational Decision Making - Songül Tolan; Daniel Kemptner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the relevance of time-inconsistent preferences in educational decision making and corresponding policies within a structural dynamic choice model. Using a novel identification approach based on exclusion restrictions, we exploit the variation in average years invested in degree attainment through various educational reforms to identify the discount factor of a decision maker with hyperbolic time preferences. We make two important research contributions. First, we estimate our model using data from the German Socioeconomic Panel (soep) and provide quantitative evidence for time-inconsistent behavior in educational decision making. Second, we evaluate the relevance of time-inconsistent behavior for the effectiveness of education policies. For this purpose, we simulate policies where time preferences may play an important role: (1) an increase in the state grant for students (BaföG) as a way to affect short-run costs while at school and (2) an increase in the state grant as a loan which will have to be payed back five years after the end of the education.
Keywords: C61; D91; I21; 330